1984
DOI: 10.1128/jcm.19.1.63-67.1984
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neisseria cinerea, a nonpathogenic species isolated on Martin-Lewis medium selective for pathogenic Neisseria spp

Abstract: This strain, NRL 32165, did not produce detectable acid from glucose, maltose, sucrose, fructose, mannitol, or lactose in either cystine Trypticase agar (BBL Microbiology Systems, Cockeysville, Md.) or modified oxidation-fermentation medium and was identified presumptively as a glucose-negative Neisseria gonorrhoeae strain, but was identified later as Neisseria cinerea on the basis of its biochemical reactions. Nitrate was not reduced, nitrite (0.001%, wt/vol) was reduced, and polysaccharide was not produced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 24 publications
0
50
0
Order By: Relevance
“…Of these 204 strains, 39 were penicillinase-producing N. gonorrhoeae. Strains were cultured on GCK medium and stored at -70°C as described previously (6).…”
Section: Methodsmentioning
confidence: 99%
“…Of these 204 strains, 39 were penicillinase-producing N. gonorrhoeae. Strains were cultured on GCK medium and stored at -70°C as described previously (6).…”
Section: Methodsmentioning
confidence: 99%
“…Correct identification of M catarrhalis from human specimens mainly entails differentiation from Neisseria meninigitidis and the apathogenic Neisseria species, but also from the other Moraxella species, all of which are members of the normal flora of the upper respiratory tract. The apathogenic Neisseria species comprise Neisseria mucosa, Neisseria pharyngis, Neisseria Jlavescens, Neisseria lactamica and Neisseria cinerea, of which especially N cinerea has been prone to misidentification as M catarrhalis because of its lack of saccharolytic capacity (Knapp et al 1984).…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…Strains of M catarrhah have been found susceptible to colistin, with inhibition zones of 3 10 mm in diameter when using disks containing lOpg of colistin (Knapp et al 1984, Morello et al 1985, but resistant strains occur, which diminishes the reliability of this characteristic (I, Blackwell et al 1978, Dillon et al 1988, Doern and Morse 1980, Durussel and Siegrist 1988, Knapp 1988, Young and Bain 1983.…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…catarrhalis." Described in German and later in French (256), N. cinerea usually was overlooked until 1984, when it was further characterized by Knapp et al (180). Two studies of bacteria isolated from throat cultures on semiselective media showed that the ratios of N. cinerealB.…”
mentioning
confidence: 99%